Penggunaan Media Power Point dalam Meningkatkan Hasil Belajar Siswa Kelas VI pada Pembelajaran Tematik - Arnita Arnita (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2021)
This study aims to determine the improvement of student learning outcomes in thematic subjects of class VI Madrasah Ibtidaiyah No. 40 /e.3 Koto Tuo Pulau Tengah Kec Keliling Danau Kerinci Regency with the application of power point media. This research is a classroom action research (CAR). The subjects in this study were students of class VI Madrasah Ibtidaiyah No. 40 /e. 3 Koto Tuo Central Island Kerinci Keliling Lake, Kerinci Regency. Data collection techniques using observation, interviews, documentation, and tests. The results showed that the use of power point media in the learning process could improve student learning outcomes. Improving student learning outcomes can be measured from the evaluation of cycle I and cycle II. The value of student learning activities in the first cycle is 56.36% and the second cycle is 88.18%. While the increase in student learning outcomes in the first cycle was 60.56 with an incomplete category with a validity of 0.528 and student learning outcomes in the second cycle of 88.89 with a complete category with a validity value of 0.577. The results of research at Madrasah Ibtidaiyah No. 40 /e.3 Koto Tuo Pulau Tengah Kec Keliling Danau Kerinci Regency has been well achieved and it is proven that power point learning media can improve student learning outcomes.